2014
DOI: 10.1111/febs.12779
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of a FeoB A143S G5 loop mutant explains the accelerated GDP release rate

Abstract: GTPases (G proteins) hydrolyze the conversion of GTP to GDP and free phosphate, comprising an integral part of prokaryotic and eukaryotic signaling, protein biosynthesis and cell division, as well as membrane transport processes. The G protein cycle is brought to a halt after GTP hydrolysis, and requires the release of GDP before a new cycle can be initiated. For eukaryotic heterotrimeric G abc proteins, the interaction with a membrane-bound G protein-coupled receptor catalyzes the release of GDP from the G a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…Furthermore, the ITC experimental results showed that the S150A mutant protein had the greatest GDP affinity ( K d =2.0 μM), approximately five times that of wild-type Ec NFeoB, which is also in agreement with a decelerated GDP release rate ( Figure 3 and Table 1 ). These molecular phenotypes conform to previous studies of Ec NFeoB [ 16 ], as well as with studies of the equivalent residue in St NFeoB [ 23 ], Gα s [ 18 ] and Gα i 1 [ 24 ]. The rationale for the altered nucleotide-binding and release properties can be inferred from our recent studies of the inverse mutant of St NFeoB [ 23 ].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, the ITC experimental results showed that the S150A mutant protein had the greatest GDP affinity ( K d =2.0 μM), approximately five times that of wild-type Ec NFeoB, which is also in agreement with a decelerated GDP release rate ( Figure 3 and Table 1 ). These molecular phenotypes conform to previous studies of Ec NFeoB [ 16 ], as well as with studies of the equivalent residue in St NFeoB [ 23 ], Gα s [ 18 ] and Gα i 1 [ 24 ]. The rationale for the altered nucleotide-binding and release properties can be inferred from our recent studies of the inverse mutant of St NFeoB [ 23 ].…”
Section: Resultssupporting
confidence: 90%
“…These molecular phenotypes conform to previous studies of Ec NFeoB [ 16 ], as well as with studies of the equivalent residue in St NFeoB [ 23 ], Gα s [ 18 ] and Gα i 1 [ 24 ]. The rationale for the altered nucleotide-binding and release properties can be inferred from our recent studies of the inverse mutant of St NFeoB [ 23 ]. The St NFeoB protein has, as most other GTPases, an alanine residue at this position ( Figure 1 B).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Recently, we reported mutational studies of the G5 loop of Escherichia coli NFeoB, which illustrated a correlation be-tween the sequence composition of the loop and the intrinsic GDP release rate (13). However, despite these observations, it is unclear whether the observed conformational changes in the G5 loop are a prerequisite for GDP release, or if the movement is a consequence of GDP release.…”
mentioning
confidence: 99%